NEURODEVELOPMENTAL SYNDROMES: EARLY INDICATORS OF SCHIZOPHRENIA AND BIPOLAR DISORDER - Tsintaraki, Alexandra; Karantzi, Venelena (Open Schools Journal for Open Science, 2025)
Schizophrenia and bipolar disorder are serious psychiatric conditions that can originate in early childhood through subtle neurodevelopmental signs. These early indicators, if recognized and treated promptly, can improve long-term outcomes. This report discusses the characteristics, causes, diagnosis, and treatment of these two major mental health disorders from a neurodevelopmental perspective.